Moving beyond non-engagement on regulated needle-syringe exchange programs in Australian prisons - Levy Michael; Mogg Daniel (Harm Reduction Journal, 2009)
Abstract Background Australia is at a fork in the road with the possibility of a needle-syringe exchange program (NSP) to be introduced at the new prison in the ACT. However, the current situation is characterised by non-engagement from major stakeholders. We explore why informed discussion will not be enough to convince prison officers, policy makers and the wider community of the benefits of prison-based NSPs. Other methods of engagement and communication will be proposed – in that may provide avenues for "breakthrough". Methods A review of the literature on needle-syringe exchanges and harm reduction strategies within the context of prisons and prisoner health was conducted. Literature on strategies to change attitudes and move beyond intractable situations was also consulted. In addition, one author, DM, conducted a two-hour interview with an ex-prison officer. Results No studies were found which investigated the potential efficacy of interventions to modify attitudes or behaviours in the specific context of introducing an NSP into a prison. Nonetheless, several theories were identified which may explain the failure of informed discussion alone to create change in this situation and may therefore lead to suggestions for engagement and communication to move towards a resolution Discussion Cognitive-behavioural therapy highlights the importance of individual cognitions and how they shape behaviours in any change campaign. Social identity theory emphasizes changes to social processes that may open the prison officer workforce to change. Peace studies also suggests socialization strategies such as observing an established and effective prison-based needle-syringe exchange. Social marketing provides suggestions on how to sell an exchange to ensuring the benefits are framed to outweigh the costs. Conclusion Psychology, peace studies and social marketing all agree people's views must be carefully collected and analysed if people are going to be convinced to consider and discuss the issue. By understanding the views and their underlying motivations of those who oppose NSPs, it will be far easier to influence these views. Furthermore, involving all stakeholders, especially prison authorities, will help create a sense of ownership of a solution and therefore increase the chances of that solution succeeding.